Déficits no comportamento de atividade física em crianças com transtorno do desenvolvimento da coordenação: revisão sistemática - Mercê, Cristiana (2022)
The Developmental Coordination Disorder (DCD) affects about 5 to 6% of school-aged children, being one of the most common developmental problems in childhood. A dated review identified that DCD children had lower levels of physical activity than their peers however, they did not investigate the implications of this lower activity in the children's lives. The present systematic review aimed to identify: i) differences in physical activity levels between children with developmental coordination disorder (pDCD) and typical development, ii) the repercussions of these differences, and iii) main instruments used in the measurement of physical activity. A comprehensive search in five databases was performed (Science Direct, PubMed, Web of Science, EBSCO, Cochrane), including grey literature. After finding 785 publications, 16 studies were included. This review verified that pDCD children have lower levels of moderate and vigorous physical activity, with possible implications at physical (e.g., higher percentages of fat mass) and psychological (e.g., increased levels of frustration) levels. This review confirms that children with pDCD are less active than children with typical development and have a higher risk of developing cardio-metabolic diseases. Parents, teachers, schools and communities should create motivational environments for youngsters with DCD to engage and maintain physical activity as they move into adulthood.